Modeling water and fertilizer use in wick irrigation system for smallholder greenhouse crop production - Shaheen, Javed (2017)
Water shortage has become the crucial issue of the current world, and it is going to be harder day by day to fulfill the food requirements of the increasing world population with the available fresh water resources using traditional irrigation systems. Therefore, there is urgent need to develop and adopt efficient irrigation methods and proper irrigation management strategies. No doubt among micro irrigation systems, drip irrigation saves a substantial amount of water and labor, increases yields, and often also improves the quality of the produce. However, the higher investment and energy cost limit the development of the low-cost irrigation system for subsistence farmers. There has been immense interest in developing new micro-irrigation systems, and wick irrigation system as promising irrigation methods to address this issue. This study, by conducting laboratory experiments, compared and confirmed hydraulic characteristics and performance of cotton-bonded nonwoven material against local materials. The performance of hanging and buried wick was compared in the laboratory and glasshouse as well. Factors, such as water level inside PVC pipe, wick length inside PVC pipe, initial volumetric water contents and pot size, related to discharge variation of the wick emitter were evaluated in the laboratory. The relationship was investigated among crop water use (ET), pot size and water level in the glasshouse. In this study, the wick emitter discharge equation was developed for both hanging and buried wick. Moreover, the wick irrigation design was developed using water circulating pump, hose pipes and PVC pipes for glasshouse to avoid algae growth and evaporation. Algae growth was observed visually, and water loss was measured before and after algae growth to evaluate the effects of algae growth on the discharge of buried wick. An experiment was carried out for tomato crop to simulate water distribution and wetting pattern using HYDRUS 2D/3D. Two water levels inside the pipe, three types of pots by size and "peatgrow” as growing media were used to develop the proper water application strategies and irrigation efficacy. Soil moisture contents were also measured. Crop nutrients management was evaluated by measuring EC and pH at a different stage of the crop using EC and pH meters, and the amount of nutrients (N, P, K, Mg, Na and Ca) was determined in leachate. The results from this study showed and proved that cotton-bonded non-woven wick material has better capillarity action, maximum capillary height and water holding capacity than local materials. The results also showed the effects of water level inside the pipe, wick length inside the pipe, pot size, ET and initial volumetric water contents on the discharge of wick irrigation system. Factors related to the wick emitter discharge used to develop equations for compensating wick emitter discharge by replacing the pressure head of a drip emitter with controlling factors of the wicking emitter. The measured water volume was close to the simulated water using wick emitter discharge equation. The results of collected ET using different methods were in order ETWBE > ETgvi > ETCROPWAT > ETgauge. Algae was observed at the end of the 3rd month with 6% decreasing effects on the discharge of buried wick. Results from this study revealed that the tomato plant growth showed insignificant differences when fresh water was used at two discharge levels. In contrast, the tomato plants growth showed differences among the pot size, in small pots roots were exceeded out from the bottom of the pot. The results obtained for EC and pH showed significant difference based on the age of the plant. The leachate was observed and the results of nutrients determination in leachate revealed the highest amount of P followed by Ca, Mg, Na, K and N. The results of simulation of water movement using HYDRUS 2D/3D disclosed the water movement of wick irrigation system in a container planted with tomatoes. The findings from this study suggested opportunities to improve an effective Capillary Wick Irrigation System (CWIS) for smallholder greenhouse production.